A STUDY ON THE RELATIONSHIPS AMONG BRAND IMAGE, SERVICE INNOVATION, WORD OF MOUTH, AND PURCHASE INTENTION: THE CASE OF ALIGN UNMANNED AERIAL VEHICLES - Linda Lin-Chin Lin; Tai-Wei Huang; Fu-Tang Chen; Yu-Hui Cheng (International Journal of Application on Economics and Business, 2026)
This study aims to examine whether brand image and service innovation influence consumers’ purchase intention through the mediating mechanism of word of mouth(WOM) in the high-technology drone industry. In this highly technology-oriented sector, firms traditionally compete based on product performance and innovative applications. However, as drone technology rapidly matures, consumers increasingly emphasize after-sales service quality, brand trust, which leads to a shift in purchase decisions from direct evaluations of brand image and service innovation toward reliance on WOM. Under such conditions, brand image and service innovation may no longer directly affect purchase intention but instead exert influence indirectly through WOM as a mediating variable. Based on this perspective, this study targets consumers in Taiwan who have experience using or intention to purchase drones from Align Technology. A quantitative questionnaire survey was conducted, and the collected data were analyzed using SPSS to examine the relationships among the research constructs. The findings further demonstrate that in high-technology and high-risk contexts, brand image and service innovation do not directly influence purchase intention but instead generate indirect effects through the social trust formed by WOM. Empirical results indicate that positive brand image and service innovation enhance purchase intention through favorable WOM.